Environmental, social and governance initiatives and wealth creation for firms: An empirical examination - Bhaskaran, Rajesh Kumar; Irene, Wei Kiong Ting; Sukumaran, Sujit K.; Sumod, Saraswathy Divakaran (John Wiley and Sons Ltd, 2020)
This study examines the effect of environmental, social, and governance (ESG) activities on firm performance of 4,887 global companies. Mean difference test shows that firms with a high level of ESG activities are different from their low‐ESG counterparts. The two‐stage least square results suggest that ESG activities on (a) the welfare for internal stakeholders and best corporate governance practices are beneficial for firm performance and (b) antitakeover mechanisms (pollution control) adopted by firms are negatively (positively) valued by market players. Overall, this is the first study to examine the effects of ESG on the market‐based and accounting‐based performance of global firms.